Negative impact of the imidazolium-based ionic liquid [C8mim]Br on silver carp (Hypophthalmichthys molitrix): Long-term and low-level exposure. (December 2018) - Ma, Junguo; Li, Xinxin; Cui, Mengke; Li, Weiguo; Li, Xiaoyu
Abstract: This study aimed to determine the chronic toxicity of the ionic liquid (IL) 1-methyl-3-octylimidazolium bromide ([C8 mim]Br) on silver carp to further study the toxicological mechanism of ILs. For this purpose, 60-d chronic exposure at concentrations of 1.09 or 4.38 mg L −1 [C8 mim]Br in silver carp was conducted. The results of biochemical assays revealed that [C8 mim]Br-treatment remarkably promoted serum lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), acid phosphatase (ACP), and alkaline phosphatase (AKP) activities, indicating that [C8 mim]Br-exposure caused fish organ damage. Long-term exposure of [C8 mim]Br also altered the activities of superoxide dismutase (SOD) and catalase (CAT) and the glutathione (GSH) level but increased malondialdehyde (MDA) levels in fish brain, gill, intestine, kidney, liver, and muscle, suggesting that [C8 mim]Br-treatment may cause oxidative stress in fish organs. Further work revealed that [C8 mim]Br-treatment increased the activities of erythromycin- N -demethylase (ERND) and glutathione S -transferases (GST), which may participate in the metabolism of [C8 mim]Br in fish liver. Moreover, chronic [C8 mim]Br-exposure remarkably promoted the expression of inducible nitric oxide synthase (iNOS), interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α), and nuclear factor-κB (NF-κB) and altered the levels of transforming growth factor-β (TGF-β), suggesting that long-term exposure of [C8 mim]Br might promote the inflammatory response in fish liver. Additionally, [C8 mim]Br-exposure altered succinate dehydrogenase (SDH) activity and promoted caspase-9 and caspase-3 activities in fish liver, suggesting that chronic [C8 mim]Br-exposure also induces hepatocellular apoptosis via the mitochondrial pathway. The results presented here may be helpful to illuminate the chronic toxicity mechanism of imidazolium-based ILs and safe use of ILs in the future. Highlights: Chronic exposure of [C8 mim]Br altered haematological parameters of silver carp. Long-term exposure of [C8 mim]Br caused oxidative stress in fish organs. The ERND and GST may be involved in the metabolism of [C8 mim]Br in fish liver. Chronic [C8 mim]Br exposure caused inflammatory reaction in fish liver. Chronic exposure induced hepatic apoptosis via mitochondria pathway.